1978
DOI: 10.2307/3897603
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics after Wildfires in Sagebrush Grasslands

Abstract: Population dynamics of herbaceous and shrub species were investigated in big sagebrush/Thurber needlegrass communities burned in wildfires. The sites burned are representative of extensive areas of degraded rangelands in the central Great Basin. Herbaceous succession after wildfires in these communities is dominated by the dynamics of populations of the alien annual grass downy brome. Downy brome caryopses are greatly reduced by most large wildfires, but the plants originating from surviving downy brome caryop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(138 citation statements)
references
References 16 publications
3
134
1
Order By: Relevance
“…Still, depending on the size of the area disturbed, and especially for very large areas, seed availability could also be a limitation to recovery (Ziegenhagen and Miller 2009). Big sagebrush seedlings are poor competitors compared to seedlings of many exotic species (Young and Evans 1978), and some authors have reported that big sagebrush seeds exist in the seed bank for only a short time period: Wyoming big sagebrush seeds were v www.esajournals.org found in the seed bank during summer of the year following seed production, but not in the subsequent winter and spring (Young and Evans 1975). In contrast, Wijayratne and Pyke (2012) found that if seeds were deeper than 3 cm in the soil, they remained viable for at least 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Still, depending on the size of the area disturbed, and especially for very large areas, seed availability could also be a limitation to recovery (Ziegenhagen and Miller 2009). Big sagebrush seedlings are poor competitors compared to seedlings of many exotic species (Young and Evans 1978), and some authors have reported that big sagebrush seeds exist in the seed bank for only a short time period: Wyoming big sagebrush seeds were v www.esajournals.org found in the seed bank during summer of the year following seed production, but not in the subsequent winter and spring (Young and Evans 1975). In contrast, Wijayratne and Pyke (2012) found that if seeds were deeper than 3 cm in the soil, they remained viable for at least 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in bluebunch wheatgrass and junegrass production after burning reported elsewhere (Uresk et al 1976, Weaver 1951, Blaisdell 1953 did not occur. Young and Evans (1978) suggested that cheatgrass which reestablished the first growing season after burning was sufficient to prevent seedling establishment of perennial grasses. By the second season, perennial forbs became well established and probably because of extensive root systems were able to dominate these previously burned sites.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, fire can be a good method to manage downy brome and Japanese brome in the appropriate situations. While fire is effective at killing most annual brome plants and seeds, their presence generally is decreased for only one season leaving a small window of opportunity to reclaim the controlled area Young and Evans 1978;Young 2000). If reclamation is not practiced, burned sites previously infested with downy brome often recover to pre-fire population levels within 3 years.…”
Section: Fire To Control Downy Brome and Japanese Bromementioning
confidence: 99%
“…If reclamation is not practiced, burned sites previously infested with downy brome often recover to pre-fire population levels within 3 years. Without management input (reclamation), downy brome populations at sites that were dominated by it before fire usually recover sufficiently during the 2 nd or 3 rd years after fire to preclude perennial grass establishment (Peters and Bunting 1994;Young and Evans 1978;Young 1994). Late spring or early summer burns usually are most effective (Mueggler 1976;Rasmussen 1994).…”
Section: Fire To Control Downy Brome and Japanese Bromementioning
confidence: 99%